Cannabinoid CB1 receptor expression in oligodendrocyte progenitors of the hippocampus revealed by the NG2-EYFP-knockin mouse - Manterola, Andrea; Chara, Juan Carlos; Aguado, Tania; Palazuelos, Javier; Matute, Carlos; Mato, Susana (Frontiers in Neuroanatomy, 2022)
Adult oligodendrocyte progenitor cells (OPCs) give rise to myelinating oligodendrocytes through life and play crucial roles in brain homeostasis and plasticity during health and disease. Cannabinoid compounds acting through CB1 receptors promote the proliferation and differentiation of OPCs in vitro and facilitate developmental myelination and myelin repair in vivo. However, CB1 receptor expression in adult OPCs in situ has not been corroborated by anatomical studies and the contribution of this receptor population to the (re)myelination effects of cannabinoids remains a matter of debate. Using electron microscopy methods applied to NG2-EYFP reporter mice we assessed the localization of CB1 receptors in OPCs of the adult mouse hippocampus. To control for the specificity of CB1 receptor immunostaining we generated transgenic mice bearing EYFP expression in NG2 glia and wild-type (NG2-EYFP-CB1+/+) and knockout (NG2-EYFP-CB1–/–) for CB1 receptors. Double immunogold and immunoperoxidase labeling for CB1 and EYFP, respectively, revealed that CB1 receptors are present in a low proportion of NG2 positive profiles within hippocampal stratum radiatum of NG2-EYFP-CB1+/+ mice. Quantitative analysis of immunogold particles in synaptic structures and NG2 profiles showed that CB1 receptors are expressed at lower density in adult OPCs than in glutamatergic cells of the rodent hippocampus. These results highlight the presence of CB1 receptors in adult OPCs thus providing an anatomical substrate for the remyelination promoting effects of cannabinoids and open a novel perspective on the roles of the endocannabinoid system in brain physiology through the modulation of NG2 glia.